Long-Term Enhancement of NMDA Receptor Function in Inhibitory Neurons Preferentially Modulates Potassium Channels and Cell Adhesion Molecules - Xia, Dan; Zhang, Xinyang; Deng, Di; Ma, Xiaoyan; Masri, Samer; Wang, Jianzheng; Bao, Shaowen; Hu, Songnian; Zhou, Qiang (Frontiers in Pharmacology, 2022)
Effectively enhancing the activity of inhibitory neurons has great therapeutic potentials since their reduced function/activity has significant contributions to pathology in various brain diseases. We showed previously that NMDAR positive allosteric modulator GNE-8324 and M-8324 selectively increase NMDAR activity on the inhibitory neurons and elevates their activity in vitro and in vivo. Here we examined the impact of long-term administering M-8324 on the functions and transcriptional profiling of parvalbumin-containing neurons in two representative brain regions, primary auditory cortex (Au1) and prelimbic prefrontal cortex (PrL-PFC). We found small changes in key electrophysiological parameters and RNA levels of neurotransmitter receptors, Na+ and Ca2+ channels. In contrast, large differences in cell adhesion molecules and K+ channels were found between Au1 and PrL-PFC in drug-naïve mice, and differences in cell adhesion molecules became much smaller after M-8324 treatment. There was also minor impact of M-8324 on cell cycle and apoptosis, suggesting a fine safety profile.